Cancer Stem Cells and Its Role in Angiogenesis and Vasculogenic Mimicry in Gastrointestinal Cancers - Lizárraga-Verdugo, Erik; Avendaño-Félix, Melisa; Bermúdez, Mercedes; Ramos-Payán, Rosalio; Pérez-Plasencia, Carlos; Aguilar-Medina, Maribel (Frontiers in Oncology, 2020)
Cancer stem cells (CSCs) are able to promote initiation, survival and maintenance of tumor growth and have been involved in gastrointestinal cancers (GICs) such as esophageal, gastric and colorectal. It is well known that blood supply facilitates cancer progression, recurrence, and metastasis. In this regard, tumor-induced angiogenesis begins with expression of pro-angiogenic molecules such as vascular endothelial growth factor (VEGF), which in turn lead to neovascularization and thus to tumor growth. Another pattern of blood supply is called vasculogenic mimicry (VM). It is a reminiscent of the embryonic vascular network and is carried out by CSCs that have the capability of transdifferentiate and form vascular-tube structures in absence of endothelial cells. In this review, we discuss the role of CSCs in angiogenesis and VM, since these mechanisms represent a source of tumor nutrition, oxygenation, metabolic interchange and facilitate metastasis. Identification of CSCs mechanisms involved in angiogenesis and VM could help to address therapeutics for GICs.